Contamination of paper points used by students during preclinical and clinical endodontic procedures - Angarita, Pilar; Angarita, Karen Mercedes (Brazilian Dental Science, 2020)
Objective: To determine the presence of facultative anaerobic bacteria in the paper points used by students and to perform a pilot test to determine whether sterilization of these materials influences their absorption capacity. Material and Methods: This study consists of two phases. The first is a descriptive phase where a representative sample of paper points (n = 72) was collected from the students and information about the points was voluntarily contributed. The points were placed in saline solution after they were collected, and mechanically shaken for 60 s. Then, 300 IU of the solution was seeded on blood agar in duplicates and incubated for 5 days under anaerobic conditions. The second phase was experimental, during which five paper points of each of the existing sizes were sterilized (Numbers: 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 70, and 80), and their capacity to absorb water was compared with that of the control or non-sterilized points. Results: The study determined that 22% (n=16) of the points were primarily contaminated by gram-positive bacilli, followed by gram-positive cocci, among which Staphylococcus epidermidis was identified. The presence of contamination was not significantly associated with the conditions of the paper points (p > 0.05). Furthermore, no significant effect (p>0.05) on the absorption capacity of these materials was detected in the sterilization test. Conclusion: Contamination was observed in the paper points used by the students, confirming the importance of implementing sterilization protocols. The sterilization protocols implemented in this study did not affect the absorption capacity of the points.KeywordsMicrobiology, Contamination; Bacteria; Anaerobic.